2022
DOI: 10.3389/fpsyt.2022.929679
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Cyberbullying Victimization and Suicidal Ideation Among Chinese College Students: The Parallel Mediating Roles of Core Self-Evaluation and Depression

Abstract: With the rapid development of science and technology, the Internet has formed a new form of aggression, which is called cyberbullying. Many studies have demonstrated that cyberbullying can cause serious damage to the physical and mental health of Chinese college students, such as depression and suicide. The main purpose of this study was to investigate the relationship between cyberbullying victimization and suicidal ideation and the parallel mediating roles of core self-evaluation and depression. A questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…A study in EU member countries showed that the rate of victimization ranged from 2.8 to 31.5%, from 3.0 to 30.6% of cyber perpetration ( Henares-Montiel et al, 2022 ). Several studies have revealed that cyberbullying may lead to anxiety, depression, loneliness, social withdrawal, substance abuse, self-harm, and suicidality ( Kwan et al, 2020 ; Giumetti et al, 2021 ; Chu et al, 2022 ; Coelho et al, 2022 ; Pichel et al, 2022 ). However, much previous research focused on teenagers, and relatively few studies were conducted on university students.…”
Section: Introductionmentioning
confidence: 99%
“…A study in EU member countries showed that the rate of victimization ranged from 2.8 to 31.5%, from 3.0 to 30.6% of cyber perpetration ( Henares-Montiel et al, 2022 ). Several studies have revealed that cyberbullying may lead to anxiety, depression, loneliness, social withdrawal, substance abuse, self-harm, and suicidality ( Kwan et al, 2020 ; Giumetti et al, 2021 ; Chu et al, 2022 ; Coelho et al, 2022 ; Pichel et al, 2022 ). However, much previous research focused on teenagers, and relatively few studies were conducted on university students.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of negative affective states, such as depression and self-encumbrance, has been found to be associated with suicidal ideation. Moreover, research suggests that the severity of school bullying experienced by adoles-cents with depressive symptoms is positively correlated with the intensity of their suicidal ideation (58,59). The aforementioned analysis reveals that the primary result of the extant investigation pertains to suicidal ideation.…”
Section: School and Social Factorsmentioning
confidence: 99%